2018
DOI: 10.1111/asj.13037
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the quality of meat (Longissimus thoracis et lumborum) from Kamieniec lambs during long‐term freezer storage

Abstract: The aim of this study was to determine changes in the quality of lamb meat (Longissimus thoracis et lumborum), which was vacuum-packaged and freezer-stored (-26°C) for 6 and 12 months. The experiment was performed on 12 male lambs of the Kamieniec Longwool breed, raised to 106 days of age. In comparison with fresh meat, thawed meat was characterized by lower ash content, higher pH, greater natural drip loss and cooking loss, and lower scores for taste intensity. Vacuum packaging and low-temperature storage pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 44 publications
2
8
0
Order By: Relevance
“…Thus, the control group (CON) showed the highest water losses. The increment in exudative losses with display, one of the main undesirable quality changes during shelf life, concurs with other research outcomes in thawed lamb . The use of active edible coatings could thus make trays appear more attractive to consumers due to the decrease in exudative losses.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…Thus, the control group (CON) showed the highest water losses. The increment in exudative losses with display, one of the main undesirable quality changes during shelf life, concurs with other research outcomes in thawed lamb . The use of active edible coatings could thus make trays appear more attractive to consumers due to the decrease in exudative losses.…”
Section: Discussionsupporting
confidence: 86%
“…36,37 WHC, pH, and color Fresh meat has been reported as showing variations compared with thawed meat due to the frozen storage process. [18][19][20]38 The lack of differences in pH after thawing is consistent with results from Pinheiro et al 19 or Muela et al, 18 who found no differences in pH after 3 to 12 months or 9, 15, or 21 months of freezing. Freezing paralyzes the metabolic processes at muscular level.…”
Section: Essential Oil Compositionsupporting
confidence: 87%
See 3 more Smart Citations